PENERAPAN KONSEP GREEN BUILDING PADA PUSAT PERBELANJAAN DI KABUPATEN BANTAENG - Wahyuni, Sri; Nursyam, Nursyam; Rahim, Rahmiani (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2025)
A shopping center is a complex of buildings with department stores and small retail shops that make it easier to buy and sell goods and services. Following a period of significant growth, infrastructure development is essential to accelerate the economic growth of Bantaeng Regency between 2021 and 2022. One of the proposed solutions is to build a shopping center using energy-efficient and green building concepts. Dalam desain pusat perbelanjaan Bantaeng Regency, konsep Green Building digunakan. Primary data was gathered through qualitative descriptive methods; secondary data was gathered from literature reviews, academic journals, articles, books, and other relevant sources. Hasil menunjukkan bahwa menerapkan prinsip-prinsip Green Building dalam desain shopping center ini dapat meningkatkan efisiensi energi, mengurangi dampak negatif pada lingkungan, dan mendukung pertumbuhan ekonomi Bantaeng Regency. Ini akan memberi pengunjung pengalaman berbelanja yang lebih ramah lingkungan dan ramah lingkungan